2011
DOI: 10.1152/ajpregu.00632.2010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression profiles indicate a primary function for microRNA during the peak of DNA replication after rat partial hepatectomy

Abstract: The liver has the unique capacity to regenerate after surgical resection. However, the regulation of liver regeneration is not completely understood. Recent reports indicate an essential role for small noncoding microRNAs (miRNAs) in the regulation of hepatic development, carcinogenesis, and early regeneration. We hypothesized that miRNAs are critically involved in all phases of liver regeneration after partial hepatectomy. We performed miRNA microarray analyses after 70% partial hepatectomy in rats under isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…Our finding of mmu-miR-207 repression is in agreement with a recent study that showed that miR-207 is down-regulated during rat liver regeneration (29).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of mmu-miR-207 repression is in agreement with a recent study that showed that miR-207 is down-regulated during rat liver regeneration (29).…”
Section: Discussionsupporting
confidence: 93%
“…microRNAs have been shown to function as negative regulators of many genes during ovary development (Carletti et al 2010, Xu et al 2011b. The regulation of Pcna expression by microRNAs has been mentioned in several studies (Han et al 2010, Sirotkin et al 2010, Raschzok et al 2011. For example, downregulation of Dicer1 was associated with enhanced expression of Pcna in human cancer cell lines (Han et al 2010), and a total of 53 microRNAs were shown to most likely repress the expression of Pcna in cultured human granulosa cells (Sirotkin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed the role of miRNAs during hepatic carcinogenesis [43] and during hepatic regeneration following partial hepatectomy. Several studies, including our own, have shown that liver regeneration is associated with specific profiles of miRNA expression changes, which can be correlated with expression changes in target genes that play important roles in liver regeneration, such as growth factors or cell-cycle regulators [44][45][46][47][48][49].…”
Section: Micrornas In the Livermentioning
confidence: 88%